2020
DOI: 10.1002/ijc.33379
|View full text |Cite
|
Sign up to set email alerts
|

Calcium channel blockers are associated with lower gastric cancer risk: A territory‐wide study with propensity score analysis

Abstract: Prior studies showed that calcium channel blockers (CCBs) could modify cancer risk, but data on gastric cancer (GC) are limited. We aimed to investigate whether CCBs could modify GC risk in Helicobacter pylori‐eradicated patients. H pylori‐infected patients with hypertension who are aged ≥50 and had received clarithromycin‐based triple therapy between 2003 and 2016 were identified from a territory‐wide healthcare database. Patients with eradication failure, GC diagnosed within 6 months after HP eradication, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 60 publications
1
3
0
Order By: Relevance
“…These adverse reactions did Analysis of cards-notifications with cases for 5 years showed that the majority of SE in the form of edemas of the legs, redness and rash on the skin, itching, tachyarrhythmias, nausea, diarrhea, developed when using Amlodipine-KV, Amlodipine-Farmak and Amlodipine-Astrafarm (table 3). SE to CA, which were recorded during the analysis of cards-notifications, coincide with the literature data [15][16][17][18]. As for amlodipine drugs, which received the largest number of reports of adverse reactions, one of the explanations may be that amlodipine drugs are the leaders of the Ukrainian pharmaceutical market and world pharmaceutical market too.…”
supporting
confidence: 65%
“…These adverse reactions did Analysis of cards-notifications with cases for 5 years showed that the majority of SE in the form of edemas of the legs, redness and rash on the skin, itching, tachyarrhythmias, nausea, diarrhea, developed when using Amlodipine-KV, Amlodipine-Farmak and Amlodipine-Astrafarm (table 3). SE to CA, which were recorded during the analysis of cards-notifications, coincide with the literature data [15][16][17][18]. As for amlodipine drugs, which received the largest number of reports of adverse reactions, one of the explanations may be that amlodipine drugs are the leaders of the Ukrainian pharmaceutical market and world pharmaceutical market too.…”
supporting
confidence: 65%
“…It has also been reported that serum copper and copper/zinc ratios are higher in patients with gastrointestinal tumors than in normal subjects (21,22), while zinc and calcium in the same cases are lower than in normal subjects (23), indicating that elevated serum copper and copper/zinc ratios may be risk factors for gastrointestinal tumors, while elevated serum zinc and calcium reduce the incidence of gastrointestinal tumors (24). Thus, both zinc and calcium were regarded as protective factors against the development of gastrointestinal tumors (25,26). It is generally believed that copper is required as an important catalytic cofactor in redox chemistry for many proteins, when present in excess, free copper ions can cause damage to cellular components (27).…”
Section: Discussionmentioning
confidence: 96%
“…Since the MAPK signaling pathway is considered an important bridge from extracellular signals to intracellular responses, relevant drugs can exert significant antitumor effects on GC through the MAPK signaling pathway ( Shao et al, 2022 ). A territory-wide study demonstrated that the utilization of calcium channel blockers was correlated to a decreased chance of developing GC, which in part reflects the link between calcium signaling pathways and GC ( Li et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%